Sheikh Mahfudz at-Tarmasi’s Thought on Islamic Education - Ratnasari, Dwi (Jurnal Pendidikan Islam, 2019)
Indonesia is a country with the largest Muslim population in the world. The role of scholars in developing and maintaining Islamic values ​​is vital. Among the scholars who play an essential role in the process is Shaykh Mahfudz at Tarmasi. This article aims to explore the traditions and intellectual networks of Shaykh Mahfudz, one of the archipelago scholars of the late nineteenth century who had a profound influence on the development of Islamic intellectual traditions in the archipelago. Despite spending his age in Mecca, he succeeded in educating Javanese clerics who were members of the Jawi community to become leaders of large pesantren in the archipelago. This research concludes that Shaykh Mahfudz is a productive ulama. The intellectual traditions and networks that he built spread to various Islamic worlds through several works he produced, and through his students who acted as transmitters of Islamic sciences from Mecca to the archipelago